2022
DOI: 10.1242/dmm.049083
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of cell models harbouring mtDNA deletions for in vitro study of Pearson syndrome

Abstract: Pearson syndrome (PS) is a rare multisystem disease caused by single large scale mitochondrial DNA deletions (SLSMDs). PS presents early in infancy and it is mainly characterized by refractory sideroblastic anaemia. Prognosis is poor and treatment is supportive, thus development of new models for the study of PS and new therapy strategies is essential. In this work we report three different cell models carrying a SLMSD: fibroblasts, transmitochondrial cybrids and induced pluripotent stem cells (iPSC). All stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…This information could play a role in genetic diagnosis: if the investigated mtDNA mutation does not show defects in cybrids, it is then possible that the patient phenotype may be caused by an unknown nuclear DNA mutation. Cybrids have been used in countless of in vitro works (Bugiardini et al , 2020 ; Hernández‐Ainsa et al , 2022 ; Schaefer et al , 2022 ). In addition, they have also been crucial for the derivation of animal models (see below).…”
Section: Models Of Mtdna Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…This information could play a role in genetic diagnosis: if the investigated mtDNA mutation does not show defects in cybrids, it is then possible that the patient phenotype may be caused by an unknown nuclear DNA mutation. Cybrids have been used in countless of in vitro works (Bugiardini et al , 2020 ; Hernández‐Ainsa et al , 2022 ; Schaefer et al , 2022 ). In addition, they have also been crucial for the derivation of animal models (see below).…”
Section: Models Of Mtdna Diseasesmentioning
confidence: 99%
“…Human iPSCs carrying large‐scale mtDNA deletions have been generated from patients affected by KSS and PMPS (Cherry et al , 2013 ; Russell et al , 2018 ; Lester Sequiera et al , 2021 ; Peron et al , 2021 ; Hernández‐Ainsa et al , 2022 ). Initial studies showed defects in hematopoietic progenitors (Cherry et al , 2013 ), but the contribution of mtDNA deletions to the disease pathogenesis in differentiated progenies has not been addressed in detail.…”
Section: Ipscs and 3d Organoids As Next‐g...mentioning
confidence: 99%
“… ABSTRACT First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Carmen Hernández-Ainsa is first author on ‘ Development and characterization of cell models harbouring mtDNA deletions for in vitr o study of Pearson syndrome ’, published in DMM. Carmen is a research assistant in the lab of Eduardo Ruiz-Pesini at Universidad de Zaragoza, Zaragoza, Spain, investigating mitochondrial DNA deletions, pathological consequences and treatments through development of new in vitro models.…”
mentioning
confidence: 99%